Making Sense of the Bible Literary Type as an approach to Understanding - Marshall D. Johnson (Grand Rapids WM.B. Eerdmans Publishing, 2002)
In this book Marshall Johnson gives students the tools needed to make sense of the Bible, a task that begins with recognizing the diverse kinds of literature found between its covers. Focusing on the eight major literary forms in the Bible -- wisdom lit
Keywords: Bible as literature. Bible (Littérature) Bijbel. Literatuur. Literaire genres. Receptie